The effect of seed size and some priming method on germination of Vicia sativa L. - Onal Asci O.; Acar Z. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The sudty was conducted to determine the effect of seed size and some priming methods on germination of common vetch. Seed was fractionated into two classes “small or large seed”. The seeds for each seed size were primed in different priming medium. Germination performance of large seed is higher than small seed. PEG solution is suitable for common vetch.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)